Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/jcm10071502
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Social Support and Its Role on Self-Perceived Health in a Representative Sample of Spanish Adults. Another Aspect of Gender Inequality

Abstract: Self-perceived health has been used as a good estimator of health status and receiving affection can be a determining factor for good self-perceived health. The aim of the present study was to assess whether lack of social support (measured through Duke scale, which ranges from 11 to 55) was associated with poorer health status measured as self-perceived health, and whether that association was different between women and men. A cross-sectional study was conducted using data from the 2017 Spanish National Heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 57 publications
2
5
0
Order By: Relevance
“…Firstly, our results show that a low educational attainment level is a risk factor for women, but not for men. In agreement with previous studies [20-22, 57], we found that women’s health is further improved by the intrinsic rewards of education, as they have fewer other resources from which they can draw in the absence of a degree. Whenever women are able to complete an education, their health is improved, often at a higher rate than for men.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Firstly, our results show that a low educational attainment level is a risk factor for women, but not for men. In agreement with previous studies [20-22, 57], we found that women’s health is further improved by the intrinsic rewards of education, as they have fewer other resources from which they can draw in the absence of a degree. Whenever women are able to complete an education, their health is improved, often at a higher rate than for men.…”
Section: Discussionsupporting
confidence: 93%
“…Educational level has been proven to be a major social determinant of health. Most analyses confirm that high educational attainment is commonly linked to improved health and increased longevity with good health, when comparisons are drawn with individuals with low levels of education [18][19][20]. However, the specifics of how the benefits of education are unevenly distributed among women and men are not sufficiently explained, and the conclusions attained are far from unanimous.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When an individual www.nature.com/scientificreports/ mentions not having this type of leisure, the chances of a negative self-assessment of health can be close to three times higher. A possible explanation for this relationship is that a worse self-rated health status is associated with less social support 28 , and individuals in solitude have a negative association with leisure activities 29 . Haemodialysis requires a routine of long hours in health services and generates difficulties in maintaining leisure activities of the social type at the same frequency and intensity experienced before the beginning of treatment, which can generate unstable psychological conditions and a decrease in the quality of life 30 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent analysis carried out in Spain among an adult population established that, for women, the association between low educational level and poor self-perceived health was particularly strong [22]. According to several cross-sectional studies, the correlation between inequality and having received a lower level of education becomes more marked in the case of women [23,24].…”
Section: Introductionmentioning
confidence: 99%